Star-epoxy mesogen with 1, 3, 5-triazine core: a model of A4B3 fractal polymerization in a liquid crystalline thermoset media. Issue 6 (4th January 2016) - Pin, Jean-Mathieu; Sbirrazzuoli, Nicolas; Sacarescu, Liviu; Mija, Alice
Abstract : Synthesis of a star-epoxy monomer and design of a hierarchically organized thermoset involving both fractal and discotic mesogen self-assembly. Abstract : A star-epoxy monomer (TriaEP) has been synthesized by the creation of a 1, 3, 5-triazine core. Its association with an aromatic di-amine reveals an A4 B3 cross-linked polymer that exhibits a complex mechanism of self-assembly. These architectural aspects, resulting from both fractal polymerization and mesophase growth, are discussed in regard to its outstanding thermo-mechanical properties.